The Effectiveness of Using Wattpad Application Towards Reading Comprehension of Recount Text at Eleventh Grade Student of Senior High School 11 Jambi - Putri, Ranti Setia; Aisyah, Siti (Universitas Batanghari Jambi, 2024)
The research aimed to find out whether the Wattpad application gives effectiveness students toward reading comprehension at the eleventh-grade students of senior high school 11 Jambi. The method of this research was quantitative research. The design of this research is quasi-experimental. The population in this research was class XI F1 (Control Class) and XI F2 (Experiment Class) at senior high school 11 Jambi as a sample this research consisted of 36 students in each class. Data collection methods in this research were tests and observations. In this method, a pre-test and post-test of the effectiveness of Wattpad application towards reading comprehension of recount text were conducted. The analysis in this research uses validity and reliability tests as well as the Wilcoxon and Mann-Whitney tests. The results showed that there was a difference between the experimental group and the control group given the use of the Wattpad application on reading comprehension of recount text of class XI students of SMAN 11 Jambi as evidenced by the results of the t-test analysis. The results of the analysis show that the value which is smaller than 0.05. The Effect Size value is 0.879 which means that the use of the Wattpad Application is effective on the reading comprehension of recount text of students of grade XI of SMAN 11 Jambi.